I want my Snooki: MTV's failed subjects and post-feminist ambivalence in and around the Jersey Shore. Issue 2 (4th March 2017) - Patrick, Stephanie
Abstract: As a sexually promiscuous and outrageously flamboyant young woman, Nicole "Snooki" Polizzi of MTV's Jersey Shore (2009–2012) could be said to be the ultimate example of Angela McRobbie's post-feminist subject. However, as pervasive as post-feminist narratives have become in popular culture, the figure of Snooki problematizes its ideal forms of femininity and meritocratic success. In this paper I argue that Snooki's potential challenges to post-feminist ideology were contained by news reporting on her at the height of her fame. This analysis posits a noteworthy divide in that those most inclined to watch/consume Snooki-as-text (the MTV audience) likely remained beyond the reach of the news media's attempt to re-inscribe hegemonic ideologies onto her star image/text. I examine the relation between Snooki-as-text (the Snooki presented on Jersey Shore ) and the extra-textual attempts to undermine her popularity and legitimacy. I frame this discussion along three axes of transgression and containment: the sexual empowerment/threat paradigm; the physical markings of class and ethnic subjectivity; and the textual boundaries of meritocratic success. Despite efforts to contain her, Snooki's short-lived success hints at an ambivalence toward post-feminism today that could help chart a revitalized form of feminist politics within youth-driven popular culture.